The imposition of participation?: the case of participatory water management in coastal Bangladesh - Dewan, C.; Buisson, Marie-Charlotte; Mukherji, Aditi (2014)
Community-based Natural Resources Management (CBNRM) has been promoted as part of the development discourse on sustainable natural resources management since the mid-1980s. It has influenced recent water policy in Bangladesh through the Guidelines for Participatory Water Management (GPWM) where community-based organisations are to participate in the management of water resources. This paper reviews the extent of success of such participatory water management. It does so by first discussing the changing discourses of participation in Bangladesh’s water policy from social mobilisation to decentralised CBNRM. Second, Bangladesh is used as a case study to draw attention to how the creation of separate water management organisations has been unable to promote inclusive participation. It argues that the current form of decentralisation through a CBNRM framework has not resulted in its stated aims of equitable, efficient, and sustainable management of natural resources; rather it has duplicated existing local government institutions. Finally, it questions the current investments into community-based organisations and recommends that the role of local government in water management be formally recognised.